Effects of shared reading aloud on emotional and linguistic learning: A longitudinal study in preschools - Paolo Di Nicola; Linda Petrucci (Ricerche di Pedagogia e Didattica, 2025)
The method of shared reading aloud has demonstrated numerous benefits in pre-school children, including comprehension of text and emotions. This longitudinal study evaluates the impact of the shared reading aloud method on a sample of preschool children in the “Strong Readers” project in the province of Parma. Using the Test of Emotion Comprehension (TEC) and the Test of Comprehension of Oral Text (TOR), we found significant improvements in the two tests used. The average TOR scores increased significantly in the first year, with more modest increases in the second. TEC scores showed significant improvements in both years. These data suggest that shared reading aloud is an effective educational tool for enhancing emotional and language skills in children.